Analysis of the impact of social media on shaping public perception of legal cases - Ranti Fortuna Pertiwi (Privietlab, 2025)
Digital social media significantly influences public opinion. Posts accompanied by additional narratives can influence the process of law enforcement. This study employs a qualitative descriptive research method. It analyzes events, facts, conditions, phenomena, and circumstances occurring during the research period by presenting what happened. The research object is the focus of the study, incorporating relevant theories. The findings conclude that social media can enhance transparency, accountability, and public participation in law enforcement. However, social media can also be a source of misinformation, defamation, and even negatively influence the judicial process. Therefore, it is important for the public, law enforcement officials, and social media users to be wise in sharing posts on social media and to be aware of the potential positive and negative impacts of such posts on the legal process. One example of a legal case impacted by the power of social media is Indonesia’s e-KTP corruption case.